Dra’ Abu el-Naga, Ägypten: Untersuchung der Grabtempel der Hoheprister des Amun Ramsesnacht und Amenophis (K93.11/K93.12) - Rummel, Ute (e-Forschungsberichte des DAI, 2023)
After the discovery of a processional causeway leading up to the tomb-temple- complex of the High Priests Ramsesnakht and Amenhotep in 2010 one major focus was put on the investigation of this lateral access which is unparalleled in Thebes so far. The findings shed new light on the ritual function of the monuments during the local religious festivals. Further excavations at the two forecourts of K93.12 provided more information on their original architecture. Moreover, restoration of the site could have been started, funded by the Cultural Heritage Preservation Programme of the Federal Foreign Office.